Analysis of anxiety in the Covid-19 pandemic - Moreno Proaño, Gilda Marianela; Ubillus Castañeda, Santiago Patricio (HUMAN REVIEW. International Humanities Review / Revista Internacional de Humanidades, 2022)
This article aims to analyze anxiety in adults from Quito, Ecuador; The sample consisted of 135 men and women between the ages of 18 and 73 who had not presented a previous diagnosis of anxiety. The Beck Anxiety Inventory (BAI) was applied and it was identified that 14% of the participants present severe anxiety, 17% moderate, 36% minimal and 33% mild, with young people presenting the highest level of severe anxiety compared to adults. In relation to physical and emotional symptomatology, concern, fear and sleep difficulties are considered.